E-COMMERCE IN CREATIVE INDUSTRY - E S Soegoto; S Purna; T P Sumitra (LPPM Universitas Bina Bangsa, 2022)
The purpose of this study is to look at the development of e-commerce that applies business strategies as it has been trending and developing lately. To support this research, we used a descriptive method by presenting tips that e-commerce had made in developing and expanding its business. The results showed that the strategy using e-commerce could be applied in businesses. From these results, it could be seen that each e-commerce has its effective strategy that enables to compete in the business world. Positively, the strategies they use can be applied to our business strategy to increase the development and trend